L’Olympisme des femmes face à l’antiféminisme sportif (1921-1936) - Florys Castan-Vicente (Genre & Histoire)
In 1928, the Amsterdam Olympic Games hosted the first athletics events for women. This commencement was immediately followed by a setback, as the IOC declared itself opposed to races over 100 m for women. Faced with the IOC’s refusal to open up more athletics events to women, women organizers and sportswomen campaigned to become part of the Olympic Games while organizing their own institution in a separatist fashion. By organizing themselves into an independent international federation (the FSFI or Fédération Sportive Féminine Internationale), they created an institution in competition with the IOC and challenged antifeminism in sport on its own turf. International competitive sport thus became a space of struggle taken up by women, workers, the middle and working classes. Indeed, the FSFI’s ambition was not limited to challenging the gender order, but also included a social dimension. The FSFI and its “World Games”, modelled on the Olympic Games, aimed to demonstrate women’s physical abilities in international events, as well as their ability to organize and manage themselves independently, without male tutelage. Throughout the life of the FSFI (1921-1936), the sports movement was under constant attack to re-establish the gender order in international sports. After an initial period of relatively favorable development for the movement (1920-1928), the attacks intensified, and by the end of the 1930s, most of the sportswomen’s organizations linked to the FSFI, and the FSFI itself, had disappeared, often as a result of a takeover by male organizations and their leaders. We will show that attacks on the FSFI, a network of independent sportswomen, are similar to anti-feminist attacks, carried out by a network of opponents from various national and international men’s federations. In turn, the focus will also be on the responses to these attacks.